Self-assessment questionnaire and clinical evaluation of bruxism in correlation with perceived stress - Solene Chanteux; Manuela Taut; Cecilia Bacali; Andrea Kui; Mona Zeinab Zuaiter; Oana Almasan; Smaranda Buduru (Amaltea Medical Publishing House, 2024)
Bruxism is a parafunctional behavior that involves clenching and grinding of the teeth, as well as increased masseters activity with or without contact with the teeth. It can happen during the day or at night. Diagnostic tools for bruxism include self-assessment questionnaires, clinical evaluation forms and polysomnography. Stress and anxiety represent two psychological factors that have been frequently related to bruxism. Twenty students in dental medicine were included in this study and a self-assessment questionnaire together with a clinical evaluation form were used as diagnostic tools for bruxism. Consequently, two groups developed: group A or non-bruxers and group B or bruxers. A questionnaire of perceived stress and anxiety levels was applied for both groups. The average score for group A was 20.8 and for group B was 31.8 with a statistically significant difference (p=0.0062, T-test). Higher perceived stress level was associated with a higher risk of bruxism, along with higher anxiety level, parafunctions, and poor sleep quality. In order to accurately diagnose bruxism, a comprehensive clinical examination and, if feasible, a polysomnography ought to be performed after completing a self-assessment questionnaire.